Microstructure and property control in TiO2–Pt nanocomposite thin films. Issue 1 (January 2015) - Lahmar, Abdelilah; Pfeiffer, Nicole; Habouti, Salah; Es-Souni, Mohammed
Abstract: We report on the synthesis of TiO2 and of TiO2 +50 wt% Pt nanocomposite under two atmospheres processed on Si-substrate. For TiO2 +50 wt% Pt thin films two different platinum precursors are used. X-ray diffraction and Raman spectroscopy allowed the identification of the formed phases.